Management of Unemployment and Employment of Youth in the Labor Market as a Factor of the Key Direction of Sustainable Development of Kazakhstan - KORGAN, Bibinur; SABIROVA, Rysty; KUNYAZOVA, Saule; ADIYETOVA, Elmira; TURDIYEVA, Zukhra; BISSEMBIYEVA, Zhanargul (Journal of Environmental Management and Tourism; Vol 13 No 1 (2022): JEMT, Volume XIII, Issue 1(57), Spring 2022, 2022)
The scale of youth employment and unemployment in Kazakhstan attracts the active attention of both public authorities, business and the population as a whole. Young people today find themselves in the risk group, as they have considerable difficulties in finding a job. State policy to support youth has proposed a large number of programs, however, able-bodied, highly qualified young people are leaving their home country in search of a better life and the remaining young people are desperate to get a job in their field, they take any job, moreover, as a result of the crisis due to the pandemic, there is a lack of jobs and they are forced to be food delivery, goods, courier mail, handing out flyers on the streets, etc. The authors conducted a study to find out the main reasons for the pessimistic attitude and the desire of the main mass of young people to leave Kazakhstan. By means of trend forecasting we revealed the dynamics of migrant youth who are easily employed abroad as good product is in high demand. This phenomenon will inevitably lead our society to degradation and inability to form a knowledge-based economy. In connection with this the authors were proposed solutions to all of the identified problems for the prospective employment of young people in the labor market in the formation of knowledge-based economy of Kazakhstan.